Improving housekeeping competencies at Sandat Living Guest House, Bali - Suyasa, Ni Luh Christine Prawitha Sari; Dewi, Putu Chrisma; Susanto, Putu Chris; Ndaparoka, Iin Saputri; Antikanol, Aldensia Nirati; Suwianjani, Kadek Ayu Intan (Universitas Muhammadiyah Magelang, 2025)
This community partnership program aims to enhance the housekeeping skills of staff at Sandat Living Guest House in Canggu, Bali. The main challenge identified by the owner-manager was the lack of formal education and training in hospitality services, particularly housekeeping, among the staff, including the manager. To address this, the training focused on implementing Standard Operating Procedures (SOPs) for room cleaning, improving knowledge of cleaning techniques, and ensuring the proper use of equipment and chemicals for both guest rooms and public areas. The training was conducted in three sessions, an initial analysis of existing housekeeping practices, followed by a practical implementation of the new SOPs, and an evaluation. The results demonstrated a significant improvement, with post-test scores showing an average increase of over 80%. This indicates a substantial gain in the staff's knowledge and practical skills. The program not only improved the quality of hospitality services at the guest house but also made a positive contribution to local tourism by enhancing the professional competence of the hospitality staff.